Assessing the impact of COVID-19 pandemic on the health of residents and the healthcare system in Alberta, Canada: an observational study—The Alberta POST-COVID Follow-up Study. Issue 2 (17th February 2023) - Chen, Xueyi; Bakal, Jeffrey; Whitten, Tara; Waldie, Barbara; Ho, Chester; Wright, Paul; Hassam, Shahin; Norris, Colleen
Abstract : Introduction: Very little is known about how the COVID-19 pandemic has affected the health of residents and the healthcare system in Alberta, Canada. The purpose of this study is to establish an observational study to characterise the health of residents in Alberta, Canada, over time, covering a population that tested negative or positive for COVID-19 during the pandemic. The primary outcome is to characterise 'long COVID-19' and the health status of residents during the COVID-19 pandemic. Secondary outcomes include the estimation of the risk of and risk factors associated with adverse health outcomes and healthcare utilisation and burdens. Methods and analysis: This is a population-level provincial observational study which will follow-up with Alberta residents who underwent testing for COVID-19 and completed surveys adapted from the ISARIC COVID-19 long-term follow-up survey. The survey data will be linked with medical records. Statistical analyses will be carried out to characterise 'long COVID-19' and the health status of residents during the pandemic. The outcomes of this study will inform strategies for primary care and rehabilitation services to prevent chronic consequences; contribute to healthcare management, interventional studies, rehabilitation and health management to reduce overall morbidity and improve long-term outcomes of COVID-19 and the COVID-19 pandemic and potentially guide a self-evaluation of a remote monitoring system to manage individuals' health. Ethics and dissemination: This study was reviewed and approved by the University of Alberta ethics committee (Study ID: Pro00112053 & Pro00113039) on 13 August 2021 and adheres to the Alberta Health Services research information management policy. Study results will be used to manage clinical care, published in peer-reviewed journals and presented at local, national and international conferences. Protocol version: 6 June 2022 EuroQol ID: 161 015.